Conflict and entrepreneurial activity in Afghanistan: Findings from the national risk vulnerability assessment data - Tommaso Ciarli; Saeed Parto; Maria Savona (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
The paper examines the relationship between conflict and entrepreneurial activity in Afghanistan, drawing upon a unique data set, the National Risk and Vulnerability Assessment household survey 2005. Afghanistan is severely underdeveloped and poor. Conflict has persisted in vast swathes of the country for decades, so that Afghanistan may be more appropriately described as an in-, rather than post-, conflict country. At the same time, qualitative (and anecdotal) evidence suggests that entrepreneurial activity is ubiquitous, although mainly due to survival strategies rather than a spirit of entrepreneurialism We empirically explore whether conflict affects the likelihood of a household to engage in entrepreneurial activity, proxied by sources of income coming from holding a small business. We control for the household characteristics and those of the environment, such as social capital, access to resources and infrastructure, as well as the presence of a minimal institutional governance system, to isolate the impact of conflict on household entrepreneurial behaviour. We find that the direct negative effect of the conflict on entrepreneurship is very small. The results on the control variables suggest that (i) the generation of entrepreneurship has seen conflict and instability for a whole life,( ii) a small business is a mean of surviving in a situation where any other support is lacking, (iii) it is a viable strategy when the household can cover some of the associated risks, (iv) there is no indirect effect of conflict via institutions and infrastructure, and (v) entrepreneurial activity may substitute for lacking markets and governance institutions. These results call for further and more in-depth research on Afghanistan as an overlooked area of study by the academic and development research community despite representing a priority for internationally supported reconstruction.
Keywords: L26; D1; O12; O15; O17; 330; entrepreneurship; conflict; Afghanistan; national risk vulnerability assessment; Politischer Konflikt; Unternehmer; Privatwirtschaft; Institutionelle Infrastruktur; Unterentwicklung; Entrepreneurship-Ansatz; Afghanistan